2016
DOI: 10.1038/bmt.2016.129
|View full text |Cite
|
Sign up to set email alerts
|

Brentuximab vedotin in combination with or without donor lymphocyte infusion for patients with Hodgkin lymphoma after allogeneic stem cell transplantation

Abstract: In our study, we evaluated the safety and efficacy of Brentuximab vedotin (BV) with or without the addition of donor lymphocyte infusion (DLI) after allogeneic stem cell transplantation (allo-SCT) in 16 patients with advanced Hodgkin lymphoma (HL). Thirteen patients with relapsed HL after allo-SCT received BV as treatment for active disease. Three patients without progression of HL after allo-SCT received BV as consolidation. Twelve patients had been previously exposed to BV for treatment of relapse after auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 16 publications
0
18
0
2
Order By: Relevance
“…Current strategies for relapsed HL after allo-HCT (summarized in Table 3) are discouraging. [19][20][21][22][23][24][25] Using different approaches (donor lymphocyte infusion with or without chemotherapy, brentuximab vedotin, or bendamustine), modest results were reported, with median PFS ranging from 6 to 18 months. Although our study did not directly compare patients treated with alternative approaches, our results would suggest at least a better risk-benefit ratio than current strategies for relapsed HL after allo-HCT: median PFS was not reached at 16 months alongside an acceptable rate of 30% GVHD and 9 (45%) long-term responders free of cGVHD whereas a majority of long-term responders developed extensive cGVHD after donor lymphocyte infusion-based approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Current strategies for relapsed HL after allo-HCT (summarized in Table 3) are discouraging. [19][20][21][22][23][24][25] Using different approaches (donor lymphocyte infusion with or without chemotherapy, brentuximab vedotin, or bendamustine), modest results were reported, with median PFS ranging from 6 to 18 months. Although our study did not directly compare patients treated with alternative approaches, our results would suggest at least a better risk-benefit ratio than current strategies for relapsed HL after allo-HCT: median PFS was not reached at 16 months alongside an acceptable rate of 30% GVHD and 9 (45%) long-term responders free of cGVHD whereas a majority of long-term responders developed extensive cGVHD after donor lymphocyte infusion-based approaches.…”
Section: Discussionmentioning
confidence: 99%
“…28 Ten of these patients also received DLI, resulting in GVHD in 7 patients. Unfortunately, we do not know the reason for the higher frequency of DLI in the BV group, but one can speculate that DLI is used for the most part in responding patients after debulking and BV might have been more successful than alternative therapies in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…16,17,[20][21][22][23] Checkpoint inhibitors are increasingly being used in this setting and appear to be highly efficacious, although with conflicting safety results because they may be complicated by the rapid onset of severe and treatment-refractory graft-versus-host disease (GVHD). 24,25 Anecdotal reports and a few small series have suggested that BV, either alone 26,27 or combined with donor lymphocyte infusion (DLI), 28 may be efficacious in the post-allograft setting.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, brentuximab vedotin has been successfully used prior to allogeneic transplantation 199,200 as a single agent or in combination with DLI for post-alloHCT relapse. 201,202 In contrast, PD-1 blockade prior to or after alloHCT may exacerbate GVHD due to prolonged or permanent inhibition of pathways with a key role in the induction of self-tolerance. 203,204 …”
Section: Transplantation Strategies For Refractory or Relapsed Hlmentioning
confidence: 99%